Slow Steps Towards Dual Earner/Dual Carer Family Model: Why Fathers do not Take Parental Leave - Karu, Marre; Kasearu, Kairi (Studies of Transition States and Societies, 2011)
The article looks at the transition of Estonian society towards dual earner/dual carer family model and focuses on fathers’ decision regarding taking their parental leave. Based on theory of planned behaviour by Ajzen, data from 20 qualitative interviews with fathers of small children are analysed to explore the beliefs fathers have when it comes to parental leave. The analysis distinguishes between two images of ‘good parenting’ that play a role in the fathers’ intention to take parental leave. First, there is an image of an outcome-oriented ‘project manager’ aﬀ ected by failure anxiety, and second, there is a much more relaxed image of a ‘good parent’ as a ‘companion’ who values everyday contact and a close relationship with the child(ren).